Determinants of balance in older women: mental health and age (European Journal of Health Research, 2020)
Older women are considered more fragile tan men. This leads to an increased risk of suffering a fall. Moreover, the mental health is directly associated with balance and therefore with falls. The objectives of the present study were: a) to determine the relationship between the static balance and gait with the mental health and the age of physically independent older women, b) to analyse if the cognitive decline determines the physical and mental parameters analysed. One hundred and twenty women between 60 and 80 years old were invited to collaborate in the study. The Katz scale was used to determine their functional Independence. The cognitive function was measured with the Mini Mental State. The one leg static balance (EEM) was measured with the One Leg Stanting Test. Gait was measured with the Timed Up and Go test. The mental health is directly associated with the Katz index (r² = 0,00317) and the EEM (r² = 0,132), and indirectly associated with the age (r² = 0,0509) and the gait (r² = 0,0822). The age is directly associated with the gait (r² = 0,115), and indirectly associated with the the Katz index (r² = 0,009) and the EEM (r² = 0,175). There were significant differences between the group with cognitive decline and the group whithout cognitive decline regarding the Katz index (P = 0,01), the mental health (P < 0,001), the EEM (P = 0,004) and the gait (P = 0,03). In conclusión, the age and the mental health predicts the one leg static balance and the gait in a physically independent old women simple. To accomplish cognitive stimulation exercises as well as static and dynamic balance exercises is recommended.